URBAN MANAGEMENT OF HISTORICAL CITYCENTERS BETWEEN THE OLD AND THE MODERN(AL-KHULAFAA STREET:( THE MOSQUE OF THE CALIPHS )A CASE STUDY) - Hadeel Mowafaaq Mahmood , Ahmed Ouf , Heidishalaby (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The civilizations and their concentration have emerged in the Arab countries and is one of the most contained countries for the civilization of thousands of years including Iraq, and the city of Baghdad, because of the establishment of its unique historical center and the presence of the largest and most rare urban design It is one of the historical cities ,and the existence of some of the city’s landmarks highlights its status and its studied architecture in all its aspects, Knowledge, culture and Give of urban identity. In this study, attention has been paid to its historic status and study a street of the caliphs that extends within an urban fabric that includes a number of archaeological and historical monuments, dating back to the Abbasid state and beyond, including the Mosque of the Caliphs. / 902-908m when ordered to establish it, andstudy the Mosque and role of urban management of the site and meet the needs and compare the current reality, and thestudy region suffers from the erosion And daef the administration of urban areas only with the support of organizations or other bodies of government cooperation requires development and legal and financial support to promote the reality of the region, and preserve its cultural identity and highlight the historical legacy unique of its kind as a design event linking the modern and old and a message to generations of the time of composition with the urban identity and distinguished in this site ,and Taking advantage of the international experience and what it went through to promote its landmarks by achieving what it has gone through to elevate the existing landmarks in the city, especially its historic centers and activating the role of urban managemen and its objectives, and centered on these monuments for future generations. Search Target. Discovering the role of urban management in historical city centers by clarifying the factors of the urban context that affect the maintenance and preservation of the design event represented by the Mosque of the Caliphs. The hypothesis of research. Urban management provides the realization of the urban context and the confirmation of the urban identity of the street of the caliphs and highlight the most important features and maintain the mosque of the caliphs and development. Research Problem . There is no clear perception of the role of urban management in the spatial context factors of historical city centerswaminhajamiealkhlfa.